The Concept of Student Characteristics in the Perspective of Hadith - Muhammad Mamba'ul Mursidin (Edumaspul: Jurnal Pendidikan, 2026)
Students have difficulties in the process of developing their potentials, all of which are caused by a lack of understanding of their characteristics, so that the learning and teaching process becomes less effective, innovative, and efficient. This study is expected to provide knowledge to readers about the many characteristics possessed by students, in addition to educating about the importance of understanding student characteristics in the teaching and learning process from the perspective of hadith. The method used in this study is qualitative with the type of library research. The data used in the study are sourced from the pole of al-sittah, Islamic Educational Philosophy towards character formation, individual differences in the learning process, the data processing process uses content analysis techniques (Content Analysis). The results of this study indicate that understanding characteristics is important for students in the process of developing and utilizing the potentials possessed by students. The development of students' potentials is influenced by the characteristics they get from two factors, the first is internal factors such as genes and given by Allah and the second is external factors in the form of social, cultural, and educational environmental influences. The benefits of understanding characteristics will also be felt by educators as a reference in the process of transferring knowledge to their students, so that the learning process becomes more effective and efficient